Plans for the first plasma operation of Wendelstein 7-X. (16th November 2015) - Sunn Pedersen, T.; Andreeva, T.; Bosch, H.-S.; Bozhenkov, S.; Effenberg, F.; Endler, M.; Feng, Y.; Gates, D.A.; Geiger, J.; Hartmann, D.; Hölbe, H.; Jakubowski, M.; et al.
Abstract: Wendelstein 7-X (W7-X) is currently under commissioning in preparation for its initial plasma operation phase, operation phase 1.1 (OP1.1). This first phase serves primarily to provide an integral commissioning of all major systems needed for plasma operation, as well as systems, such as diagnostics, that need plasma operation to verify their foreseen functions. In OP1.1, W7-X will have a reduced set of in-vessel components. In particular, five graphite limiter stripes replace the later foreseen divertor. This paper describes the expected machine capabilities in OP1.1, as well as a selection of physics topics that can be addressed in OP1.1, despite the simplified configuration and the reduced machine capabilities. Physics topics include the verification and adjustment of the magnetic topology, the testing of the foreseen plasma start-up scenarios and the feed-forward control of plasma density and temperature evolution, as well as more advanced topics such as scrape-off layer (SOL) studies at short connection lengths and transport studies. Plasma operation in OP1.1 will primarily be performed in helium, with a hydrogen plasma phase at the end.